State of the art Raman techniques for biological applications - Rae, Alasdair; Stosch, Rainer; Klapetek, Petr; Hight Walker, Angela R; Roy, Debdulal (Methods, 2014)
Raman spectroscopy is a powerful tool for the elucidation of qualitative and quantitative information from biological systems and has huge potential in areas such as biotechnologies, drug discovery, agro-chemical research and clinical diagnostics. This report summarises the principal Raman techniques applied to biomedical systems and discusses the challenges that exist to the wide spread adoption of Raman spectroscopy.
Keywords: Humans; Optics and Photonics; optika a fotonika; Spectrum Analysis, Raman; Ramanova spektroskopie; nelineární dynamika; lidé; Nonlinear Dynamics